META ANALYSIS: THE INFLUENCE OF THE USE OF PhET VIRTUAL MEDIA IN SCIENCE LEARNING ON STUDENTS’ CRITICAL THINKING - Tiara Jill Carissa Febrianti; Hadma Yuliani; Nadia Azizah (Jurnal IPA Terpadu, 2024)
This study investigates how much influence the use of virtual PhET media has on students' critical thinking understanding in science learning. The research method used meta-analysis. Searches were conducted on the mendeley website, Google Schoolar, reference management software, and Harzing application with the keywords "influence", "virtual PhET", and "critical thinking". The results included 30 research journal articles and found 9 research journal articles that fit the meta-analysis method. The results showed that the effect size was high, with an average of (1.31), and the interpretation of the effect size showed that the use of virtual PhET media had an 88% influence on students' critical thinking in science learning. In conclusion, the use of PhET virtual media has an impact on students' critical thinking in science learning.